Aidi injection inhibits the migration and invasion of gefitinib-resistant lung adenocarcinoma cells by regulating the PLAT/FAK/AKT pathway - Zhang, Jingyuan; Yang, Siyun; Chen, Xiaodong; Zhang, Fanqin; Guo, Siyu; Wu, Chao; Wang, Tieshan; Wang, Haojia; Lu, Shan; Qiao, Chuanqi; Sheng, Xiaoguang; Liu, Shuqi; et al. (Chinese medicine, 2025)
With extended gefitinib treatment, the therapeutic effect in some non-small cell lung cancer (NSCLC) patients declined with the development of drug resistance. Aidi injection (ADI) is utilized in various cancers as a traditional Chinese medicine prescription. This study explores the molecular mechanism by which ADI, when combined with gefitinib, attenuates gefitinib resistance in PC9GR NSCLC cells. In vitro and in vivo pharmacological experiments were conducted in PC9GR cells and NSG mice with PC9GR cell-derived tumors, respectively. The molecular mechanism of ADI was further studied using whole-transcriptome sequencing technology. Bioinformatics and molecular biology methods were employed to validate the critical targets of ADI. Firstly, ADI treatment alone and combined with gefitinib significantly inhibited the proliferation, migration, and invasion of PC9GR cells. Then, whole-transcriptome sequencing and bioinformatics analysis revealed that PLAT is a key target for the increased efficacy of ADI combined with gefitinib. Additionally, ADI downregulates the expression of PLAT, TNC, ITGB3, p-AKT, p-PI3K, and p-FAK. ADI inhibits the migration and invasion of PC9GR cells by regulating the PLAT/FAK/AKT pathway. Aidi injection inhibits the migration and invasion of gefitinib-resistant lung adenocarcinoma cells by regulating the PLAT/FAK/AKT pathway. This study provides essential evidence for elucidating the mechanism of ADI in synergistic therapy for lung cancer.